Estimation of Equilibrium Real Exchange Rate and of Deviations for Romania - Moisa Altar; Lucian Liviu Albu; Ionut Dumitru; Ciprian Necula (Romanian Academy, National Institute for Economic Research, 2009)
Equilibrium real exchange rate provides useful information on the harmonisation of convergence criteria with exchange rate stability criteria; a requirement for accession to the European Monetary Union. This study applies econometric procedures for identifying the equilibrium real exchange rate in Romania and its tendency. * Study within the CEEX Programme Project No. 220/2006 Economic Convergence and Role of Knowledge in Relation to the EU Integration ; Instiutul European din Romania PAIS III; Studiul nr. 2/2005.
Keywords: F33; F43; O23; O57; 330; Capital account; exchange rate; European integration